Frequency Of Common Waterborne Diseases in the Pediatric Department Of Abbasi Shaheed Hospital, Karachi - Salahuddin, Muhammad; Mustafa, Sultan; Masood, Shaheen; Mumtaz, Sana; Shah, Muhammad Ali; Ali, Ahsan (Biological and Clinical Sciences Research Journal, 2025)
Waterborne diseases remain a leading cause of childhood morbidity in developing countries, particularly in urban centers with poor sanitation and contaminated water supplies. Objective: To determine the frequency and distribution of common waterborne diseases among pediatric patients admitted to the Department of Pediatrics, Abbasi Shaheed Hospital, Karachi. Methodology: This descriptive cross-sectional study was conducted in the Department of Pediatrics at Abbasi Shaheed Hospital, Karachi, from February 1, 2024, to January 31, 2025. A total of 155 children, aged one month to fifteen years, presenting with clinical features suggestive of waterborne diseases, were included through non-probability consecutive sampling. Demographic data, clinical features, laboratory findings, and disease categorization were recorded using a structured proforma. Results: The mean age of the patients was 6.2 ± 3.7 years, with the majority (42.6%) belonging to the 2–5 year age group. Males accounted for 54.2% of the cases, and females accounted for 45.8%. Acute gastroenteritis was the most frequent diagnosis (44.5%), followed by enteric fever (23.9%), dysentery (16.1%), viral hepatitis A/E (9.0%), and cholera (6.5%). Seasonal analysis revealed a peak incidence during the monsoon months (37.4% of cases). Moderate to severe dehydration was observed in 61.3% of patients, while 11.6% required prolonged hospitalization. Conclusion: Waterborne diseases constitute a significant burden among pediatric patients in Karachi, with acute gastroenteritis and enteric fever being the most common. The high proportion of cases during the monsoon season underscores the impact of poor sanitation and water contamination